Metotrexato y su Uso en el Tratamiento de Enfermedades Reumáticas - Sandoval, David (1996)
The authors review methotrexate use in Rheumatic Diseases, specially in Rheumatoid arthritis. Pharmacokinetics, efficacy, toxicity, and treatment monitoring of methotrexate are presented.